2021
DOI: 10.3389/fneur.2021.731566
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Perampanel as Adjunctive Therapy in Chinese Patients With Focal-Onset Seizures: An Observational, Prospective Study

Abstract: Purpose: To evaluate the efficacy and tolerability of adjunctive perampanel (PER) in Chinese patients with focal-onset seizures, with or without secondarily generalized tonic-clonic seizures.Methods: Fifty-six patients aged 14–72 years were recruited consecutively in this single-center prospective observational study. All patients received PER as add-on treatment on the basis of clinical judgment. Seizure frequency, adverse events (AEs), and retention rates were obtained at 3 and 6 months after PER introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 33 publications
3
28
0
1
Order By: Relevance
“…Rohracher et al 19 discovered that a lower likelihood of seizure freedom was associated with enzyme-inducing antiseizure medications (75%) and late (vs early) perampanel add-on (58%). However, unlike the 3 abovementioned reports, the report by Zhang et al 13 confirmed that patients taking enzyme-inducing antiseizure medications with perampanel had a higher maintenance dose than those taking non–enzyme-inducing antiseizure medications (5.3 vs 4.5 mg), but had no reduced perampanel efficacy in seizure control. Our study also demonstrated that there were no significant statistical differences in maintenance dose and response rates between patients taking enzyme-inducing antiseizure medications with perampanel and those taking non–enzyme-inducing antiseizure medications (0.2 ± 0.1 vs 0.2 ± 0.1 mg/kg / d, P > .05).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Rohracher et al 19 discovered that a lower likelihood of seizure freedom was associated with enzyme-inducing antiseizure medications (75%) and late (vs early) perampanel add-on (58%). However, unlike the 3 abovementioned reports, the report by Zhang et al 13 confirmed that patients taking enzyme-inducing antiseizure medications with perampanel had a higher maintenance dose than those taking non–enzyme-inducing antiseizure medications (5.3 vs 4.5 mg), but had no reduced perampanel efficacy in seizure control. Our study also demonstrated that there were no significant statistical differences in maintenance dose and response rates between patients taking enzyme-inducing antiseizure medications with perampanel and those taking non–enzyme-inducing antiseizure medications (0.2 ± 0.1 vs 0.2 ± 0.1 mg/kg / d, P > .05).…”
Section: Discussionmentioning
confidence: 84%
“…Zhang et al 13 confirmed the good efficacy and tolerability of adjunctive perampanel in 56 patients aged 14-72 years with focal-onset seizures, with or without combined generalized and focal seizures.…”
mentioning
confidence: 88%
“…Furthermore, lower doses of combination therapy were also available. [ 30 ] A sudden drop in seizure-freedom rates were observed at the 3-week study timepoint, which may have been due to the titration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a prospective real-life study in China confirmed the satisfactory efficacy and tolerability of adjunctive PER in patients ≥14 years of age with focal-onset seizures. However, plasma concentrations of PER were not measured in the study, and the author concerned that they could not precisely assess the influence of concomitant enzyme inducers on the plasma levels of PER associated with seizure control and AEs [41]. Another retrospective observational study has suggested the effectiveness and safety of PER in Chinese pediatric patients (2-14 years) with refractory epilepsy [42].…”
Section: Plasma Concentrationsmentioning
confidence: 99%